Programa “Neuromat” para desarrollar la noción de número y cantidad en niños de 5 años de la institución educativa Nº80070 -Virú - Reyna Alvarado, Tania Libertad (2020)
ABSTRACT The purpose of this research is to determine to what extent the "Neuromat" program develops the notion of number and quantity in 5-year-old children of educational institution N ° 80070-Virú. For this research study, a sample consisting of 48 children and girls with different characteristics was selected. The type of research was applied with pre and post test and the design was quasi experimental with control group and experimental group; the results of the pretest show us the existence of certain deficiencies in the aspects evaluated in the evaluation test, where it was obtained that in the experimental group the children are 66.7% are in an average level and 33.3% in a low level in relation to the development of the notion of number and quantity. After having applied the "Neuromat" program, the children showed a significant increase in the development of the notion of number and quantity, with 83.3% at high level and 16.7% at medium level, concluding that the application of the program has influenced significantly in the development of number and quantity in children of 5 years of educational institution Nº. 80070-Virú, subject of research.